Evaluasi Program Billingual di Pondok Pesantren Darunnajah 2, Cipining Bogor - Ihwan Mahmudi; Yogi Saputra (At-Ta'dib, 2018)
Program evaluation is a sequence of activity which is done on purpose and carefully to know the implementation level or success of a program for knowing the effectivity of each component, for on going program or not. Billingual program in Pondok Pesantren Darunnajah Bogor, is one of program which is done structurally and sistematically run by  language department of pondok. This evaluation is aim to evaluate the implementation of billingual program in Pondok Pesantren Darunnajah 2 Cipinang Bogor reviewed form these aspects: 1) urgency (Context) program, 2) resource (Input) program, 3) Implementation (process) program and 4) result (Product)  program. This research used CIPP Model as an approach and oriented to measure program achievement level or activity by the target group, or measure the implementation result of Context, Input, Process, Product (CIPP). The research design used is descriptive design, and used observation technique, interview, and documentation. Based on the result of the research, it shows that overall achievement in Pondok Pesantren Darunnajah Cipinang Bogor in organizing billingual program with 89.9% and it categorized as a good achievement. The percentage of success achievement program in detail is context program with 100% (excellent), resources (input) program 93.3% (very good), implementation (process) program 91.4% (very good), and result (product) program 75% (moderate).